2021
DOI: 10.1002/anie.202110809
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Polar and Non‐Polar Contributions to Aromatic Stacking Interactions in Solution

Abstract: Aromatic stacking interactions have been a matter of study and debate due to their crucial role in chemical and biological systems. The strong dependence on orientation and solvent together with the relatively small interaction energies have made evaluation and rationalization a challenge for experimental and theoretical chemists. We have used a supramolecular cage formed by two tris(pyridylmethyl)amines units to build chemical Double Mutant Cycles (DMC) for the experimental measurement of the free energies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
(92 reference statements)
0
24
0
Order By: Relevance
“…However, the complex nature of solvation makes effects sometimes difficult to predict 1,2 . A large number of studies have been published to resolve the effects of solvents on non‐covalent interactions, including hydrogen bonds (H‐bond), 1–8 halogen bonds (X‐bond), 4,8–13 and dispersion interactions 14,15 . The studies show a variable response of the non‐covalent complex stabilities to solvents, as shown, for example, in Robertson et al 4 In this paper, the authors were able to control the competition between the hydrogen and halogen bond formations by changing the solvent properties and found that the studied systems prefer the formation of hydrogen bonds in nonpolar solvents.…”
Section: Introductionmentioning
confidence: 83%
“…However, the complex nature of solvation makes effects sometimes difficult to predict 1,2 . A large number of studies have been published to resolve the effects of solvents on non‐covalent interactions, including hydrogen bonds (H‐bond), 1–8 halogen bonds (X‐bond), 4,8–13 and dispersion interactions 14,15 . The studies show a variable response of the non‐covalent complex stabilities to solvents, as shown, for example, in Robertson et al 4 In this paper, the authors were able to control the competition between the hydrogen and halogen bond formations by changing the solvent properties and found that the studied systems prefer the formation of hydrogen bonds in nonpolar solvents.…”
Section: Introductionmentioning
confidence: 83%
“…A range of different supramolecular systems have been developed to quantify aromatic interactions in organic solvents. 9–38 Experimental measurements of substituent effects on both edge-to-face and stacking interactions using chemical double mutant cycles and molecular torsion balances correlate well with Hammett substituent constants, confirming a major role for electrostatic interactions in aromatic interactions in non-polar solvents. However, it is not clear whether such effects persist in more polar solvent environments like water.…”
Section: Introductionmentioning
confidence: 85%
“…S112 †). 13,23 There is no relationship between Hammett substituent constants and the values of DDG°measured in water for the aromatic interactions in complex A (see Fig. S113 †).…”
Section: Chemical Double Mutant Cycle Analysismentioning
confidence: 99%
“…This view received experimental support from, among others, Cockroft and co-workers, , who applied Wilcox-type molecular balance experiments to show that the intramolecular aggregation propensity between two alkyl chains of the molecular balance depended comparably little on the competitive LDIs between the alkyl chains and the solvent and more on the cohesive energy density of the solvent (solvophobic effect); if the LDIs between the alkyl chains were dominant, the aggregation tendency should have varied systematically and strongly with the competitive LDIs of the chains with the solvent, which could have been projected from their refractive indices (eq ). Recently, Zonta and co-workers have pointed to aryl–aryl stacking as being special; they advanced geometrical arguments for aryl–aryl interactions that were similar to those in Figure a,b and related them to increased nonpolar interactions . However, there is no reason why exceptions should be limited to aryl compounds.…”
Section: Attenuation Of London Dispersion Interactions In Solution An...mentioning
confidence: 99%